Protected areas, tourism development and poverty in Bangladesh - Islam, Faridul; Carlsen, Jack (School of Management, University of South Australia, 2011)
Surprisingly, limited academic attention has been paid to the relationship between protected areas, tourism development and poverty reduction in developing country contexts. The complex and dynamic interconnections between protected areas, tourism development and poverty in Bangladesh is the main focus of this paper. The paper is based on a case study of two protected areas of Bangladesh, Lawachara National Park and Satchari National Park, part of the Nishorgo Project of the Forest Department. The case study demonstrates that a co-management approach involving government agencies, non-governn1ental organisations (NGOs) and the local community can control environmental degradation due to firewood collecting, illegal logging and hunting. Co-management can also lead to alternative income generation through ecotourism which can then provide opportunities for poverty alleviation. However, these alternative income generation opportunities require adequate training for the local community members, as well as ongoing business support. Another issue is the provision of alternative fuel supplies to the adjacent villagers in order to prevent firewood collection in protected areas. Development of ecotourism can contribute to conservation through prevention of environmental degradation and through alternative income generation and hence, poverty alleviation. However an inclusive, consistent and comprehensive approach needs to be promoted if the opportunities are to be fully realised.